Ninja Writing: The Four Levels of Writing Mastery. - Raja, Shani (linkedin.com, 2018)
Explore tactics that can dramatically improve your writing. Learn about the power of the four levels—narrative, paragraphs, sentences, and words—to make your writing stand out.